Immunometabolic crossroads: infections as bidirectional modulators in diabetes and metabolic syndromes - Islam, Md. Sharifull; Monir, Sawda Binte; Haque, Nabila; Vabna, Marshia Ahmed; Fan, Jie; Li, Yikui; Nime, Ishatur; Feroz, Farahnaaz; Acharjee, Mrityunjoy; Pan, Fan (Frontiers in Endocrinology, 2025)
Diabetes and metabolic disorders represent a global health crisis driven by complex interactions between metabolic, immune, and microbial networks. Beyond their metabolic derangements- hyperglycemia, insulin resistance, and low-grade systemic inflammation-these disorders are now recognized to exist at an immunometabolic interface profoundly influenced by infectious agent The bidirectional relationship between infections and metabolic dysregulation highlighting how acute and chronic infections contribute to insulin resistance, β-cell dysfunction, and systemic inflammation, while metabolic dysregulation impairs immune competence, predisposing individuals to recurrent and severe infections. Pathogens such as Helicobacter pylori Staphylococcus aureus, Escherichia coli, SARS-CoV-2, and hepatitis viruses, alter host metabolic signaling through inflammatory, mitochondrial, and hormonal pathways, reshaping glucose and lipid homeostasis. In turn, diabetic immune impairment amplifies susceptibility to pneumonia, urinary tract infections, and chronic wound infections, reinforcing a pathogenic feedback loop. Emerging therapeutic strategies including nanotechnology enabled, therapeutics, gene, and stem cell based interventions and next-generation incretin agonists- including tirzepatide and CagriSem offer promising avenues to restore both metabolic balance and immune resilience. Additionally, foundational strategies such as lifestyle modifications, medical nutrition therapy, and vaccination remain essential components of disease control. Understanding infections as dynamic modulators of metabolic homeostasis reframes diabetes not merely as an endocrine disorder, but as a systemic immunometabolic disease. This review synthesizes current evidence on infection induced metabolic syndrome, immune impairments, and innovative therapeutic strategies to guide future precision interventions at the infection-metabolism interface.